2020
DOI: 10.31729/jnma.5216
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibiotic Susceptibility among Bacterial Isolates in Neonatal Intensive Care Unit of a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Neonatal sepsis is a major cause of neonatal morbidity and mortality worldwide, especially in developing countries like Nepal. Antibiotic resistance among microorganisms poses new challenges in the treatment of neonatal sepsis. The present study is conducted with the objectives of determining clinico-bacteriological profile and antibiotic susceptibility among isolated bacteria in a neonatal intensive care unit. Methods: A descriptive cross-sectional study was conducted from January 1, 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
4
1
0
Order By: Relevance
“…This confirms reports from a related study among neonates where Staphylococcus epidermidis and Staphylococcus haemolyticus showed poor sensitivity (13.5%) to ampicillin [ 33 ]. High resistance exhibited by Gram-positive organisms to ampicillin and penicillin corroborates other similar studies [ 34 39 ]. Further analysis showed that Klebsiella isolates were resistant to cefotaxime, a commonly used second-line antibiotic.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms reports from a related study among neonates where Staphylococcus epidermidis and Staphylococcus haemolyticus showed poor sensitivity (13.5%) to ampicillin [ 33 ]. High resistance exhibited by Gram-positive organisms to ampicillin and penicillin corroborates other similar studies [ 34 39 ]. Further analysis showed that Klebsiella isolates were resistant to cefotaxime, a commonly used second-line antibiotic.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with findings from Saudi Arabia (27/40; 67.5%) [24], and China (57,49%) [25]. However, Gram-negative bacilli were the predominant bacteria isolatedin anothers countries like Congo [15], Nigeria [9], Cameroun [26], and Nepal [27]. CoNS (28.04%) was the predominant bacteria identified in our study followed by Klebsiella pneumoniae (26,83%).…”
Section: Discussionsupporting
confidence: 90%
“…This rate is comparable to a study performed in Dessie (Ethiopia) [36]. Higher rates were found by Chaudhary [27], Agarwal [38], and Pokhrel [39].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another study from Nepal performed among 71 CoNS strains also reported similar resistance rates of the isolates toward penicillin (90%), co-trimoxazole (60%), and azithromycin (60%), and absolute sensitivity to vancomycin and linezolid [30]. Such higher occurrences of antibiotic-resistant isolates in these studies, including ours, could be attributable to the biofilm-forming tendency of the isolates or the dissemination of plasmids carrying antibiotic-resistant genes via the quorum sensing phenomenon [29,31].…”
Section: Plos Onesupporting
confidence: 78%